Mountains of inequality: encountering the politics of climate adaptation across the Himalaya - Chakraborty, Ritodhi; Rampini, Costanza; Sherpa, Pasang (Ecology and society, 2023)
There has been a widespread call for the development of transformative adaptation knowledge and strategies in the Himalayan region because of the intensifying onset of climate change impacts. But such transformative thinking is absent in much of Himalayan climate knowledge production, which builds on environmental deterministic and techno-managerial renditions of exceptional precarity; advocates for an increase in the scientific and expert driven projects on the ground; and remains rooted in the scalar realities of the nation-state. This paper contributes to the rich scholarship that counterbalances depoliticized renditions of climate change adaptation, by presenting “everyday stories of adaptation” that have emerged from the authors’ work alongside Himalayan communities. In this work we ask, who is the subject in Himalayan climate adaptation discourse and policies? And how can their stories help us envision an adaptation praxis, which challenges regional narratives of crisis and provides alternatives to climate reductionist thinking/planning, by foregrounding the intersectionality and plurality of communities and ecologies? The stories come from three parts of the Himalaya: Uttarakhand, Khumbu, and Assam, and highlight the daily labor for adaptation and its mercurial relationship with the labor for survival. We find that intertwined with changing climate-society relationships are, historical caste privileges and changing generational relationships to land; the complicated engagements between indigeneity, communal sovereignty, and exclusionary institutional mandates; and life with ethnoreligious othering in an aqueous and geopolitically fluid borderland. Together these stories witness the relational social-ecological worlds of regional inhabitants, challenging their powerless and pejorative depictions through climate reductive framings. We conclude with a set of objectives to enable more hopeful and just adaptation futures.